Effects of marijuana use on impulsivity and hostility in daily life. (1st March 2015) - Ansell, Emily B.; Laws, Holly B.; Roche, Michael J.; Sinha, Rajita
Highlights: Marijuana use was associated with increased impulsivity relative to non-use days. Increased impulsivity was also observed for the day following marijuana use. Marijuana use was associated with greater hostile perceptions and behaviors. Findings highlight the relevance of studying real world effects of marijuana use. Abstract: Background: Marijuana use is increasingly prevalent among young adults. While research has found adverse effects associated with marijuana use within experimentally controlled laboratory settings, it is unclear how recreational marijuana use affects day-to-day experiences in users. The present study sought to examine the effects of marijuana use on within-person changes in impulsivity and interpersonal hostility in daily life using smartphone administered assessments. Methods: Forty-three participants with no substance dependence reported on their alcohol consumption, tobacco use, recreational marijuana use, impulsivity, and interpersonal hostility over the course of 14 days. Responses were analyzed using multilevel modeling. Results: Marijuana use was associated with increased impulsivity on the same day and the following day relative to days when marijuana was not used, independent of alcohol use. Marijuana was also associated with increased hostile behaviors and perceptions of hostility in others on the same day when compared to days when marijuana was not used. These effects were independent of frequency of marijuana use or alcohol use. There were no significant effects of alcohol consumption on impulsivity or interpersonal hostility. Conclusions: Marijuana use is associated with changes in impulse control and hostility in daily life. This may be one route by which deleterious effects of marijuana are observed for mental health and psychosocial functioning. Given the increasing prevalence of recreational marijuana use and the potential legalization in some states, further research on the potential consequences of marijuana use in young adults' day-to-day life is warranted.